1969
DOI: 10.1128/jb.98.3.930-937.1969
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Responses of the Rat toMycoplasma arthritidis

Abstract: Arthritis was produced in rats by the intravenous injection of Mycoplasma arthritidis. Metabolic inhibiting antibody and indirect hemagglutinating antibody could not be detected in the sera of arthritic or convalescent animals. Nonmurine species of mycoplasma were capable of inducing metabolic inhibiting antibody in the rat. A hypothesis based upon the possible occurrence of heterogenetic antigens common to M. arthritidis and rat tissue was brought forward to explain these findings. Complement-fixing antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
43
0

Year Published

1970
1970
2002
2002

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 22 publications
3
43
0
Order By: Relevance
“…It has been suggested that in certain other mycoplasma-induced arthritides, chronicity is dependent upon retention of organisms (25). In murine arthritis the persistence of mycoplasmas may be due to the inability of these animals to produce sufficient neutralizing, or MI, antibodies to clear the organisms from joint tissues (26)(27)(28)(29). In the rabbit disease described in this report, however, other mechanisms of chronic inflammation must be sought to explain the continuation of disease activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that in certain other mycoplasma-induced arthritides, chronicity is dependent upon retention of organisms (25). In murine arthritis the persistence of mycoplasmas may be due to the inability of these animals to produce sufficient neutralizing, or MI, antibodies to clear the organisms from joint tissues (26)(27)(28)(29). In the rabbit disease described in this report, however, other mechanisms of chronic inflammation must be sought to explain the continuation of disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Three rabbits from the M arthritidis-injected group, 3 from the M pulmonis-injected group, 1 from the broth-injected group, and 1 normal control animal were killed at intervals of 1,2,4,7,12,20,31, and 52 weeks postinoculation. In addition, 8 rabbits each from the mycoplasma-injected groups and 7 from the broth-injected group were set aside for observation throughout the entire year and were bled for immunologic studies at intervals of 1,3, and 5 days and 1,2,3,4,7,12, 16,20,26,31,42, and 52 weeks postinoculation. Tissues were removed at autopsy for microbiologic, histologic, and immunologic examination as described previously (1).…”
mentioning
confidence: 99%
“…Rat arthritis induced by Mycoplasma arthritidis has been studied extensively in relation to clinical and histological characteristics (10,24,27,34). The immunological responses of the host have been described (5,15,17), and it has recently been suggested that a heterogenetic antigen common to M. arthritidis and rat tissue may play a role in the pathogenesis of this disease (5). In spite of these studies, many questions remain unanswered, such as the mechanism of immunity to reinfection and the pathogenesis of the spontaneous and experimental disease.…”
mentioning
confidence: 99%
“…Williams particularly interesting in view of the fact that this species produces arthritis in rats. M arthritidis also produces a chronic proliferative arthritis of mice with periods of exacerbation and remission, and the histopathology of this disease closely resembles that of human RA (31,32).…”
Section: Discussionmentioning
confidence: 84%
“…T h e presence or absence of circulating antibodies has been used as evidence for or against a It should be pointed out that failure to detect antibodies against a particular species does not necessarily indicate the absence of that organism, since we have shown that MI antibodies cannot be detected in rats experimentally infected with M arthrztidis (31).…”
Section: Discussionmentioning
confidence: 99%